Micronutrient Dynamics in Green Crop Processing: Profiling Mineral Retention in LPC and PCR from Tropical Legumes - Poonam Kale; Babita Sakdeo (The Bioscan, 2025)
This study investigated the mineral retention efficiency of green crop fractionation (GCF) in producing leaf protein concentrate (LPC) for human nutrition and pressed crop residue (PCR) for animal feed. A study was conducted to determine the levels of magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn) in four leguminous plants: Vigna unguiculata L., Lablab purpureus L., Cajanus cajan L., and Vigna radiata L. Results indicated superior iron retention in LPC, particularly from Vigna radiata (L.) (7.45 mg/g). Significant iron content was also observed in PCR, with Vigna radiata (L.) PCR retaining 5.55 mg/g. Copper distribution in LPC was relatively uniform across species (mean = 0.70 ± 0.06 mg/g), while its concentration in PCR varied, notably high in Lablab purpureus (L.) (0.87 mg/g). Zinc and magnesium generally exhibited higher retention in LPC compared to PCR. These findings highlight Vigna radiata (L.) as a promising candidate for iron biofortification and underscore species-specific mineral partitioning between LPC and PCR. Such insights are important when creating strategies to combat micronutrient malnutrition and optimize the utilization of agricultural by-products.